Differences in manioc diversity among five ethnic groups of the Colombian Amazon - Peña-Venegas, Clara P; Stomph, Tjeerd Jan; Verschoor, Gerard; Becerra López Lavelle, Luis Augusto; Struik, Paul C. (MDPI, 2014)
Manioc is an important root crop in the tropics and the most important staple food in the Amazon. Manioc is diverse but its diversity has not yet been clearly associated with environmental or social factors. Our study evaluates how variation in edaphic environments and in social factors influences manioc diversity among five ethnic groups of the Amazon region of Colombia. Inventories of landraces, genetic analysis of manioc diversity, visits to farmers’ swiddens and interviews with farmers were carried out during two years of field work. Morphotypic and genotypic diversity of manioc were large. The different ethnic groups of our study cultivate different sweet and bitter manioc landraces which they select and maintain in accordance with their ancestral rules and norms. Differences in available environments among indigenous communities (such as the presence of different soils) did not markedly affect manioc morphotypic or genotypic diversity, while social factors considerably influenced observed manioc diversity. Manioc diversity was explained by two parallel processes of manioc diversification: volunteer seedling selection and manioc seed exchange. We argue that, for a full understanding of manioc diversity, indigenous knowledge, as well as morphological and genetic variation should be taken into account.